Effectiveness of the Analgesia Nociception Index Monitoring in Patients Who Undergo Colonoscopy with Sedo-Analgesia - (:unkn) unknown (AVES, 2020)
Objective: The objective of this study was to improve the patient comfort and safety during procedures done under anaesthesia and sedation. The analgesia nociception index (ANI) noninvasively provides information on the nociception-antinociception balance, and it can be used to assess analgesia objectively. We aimed to compare the effects of analgesia management with conventional methods and with ANI monitoring on total opioid consumption, sedation and analgesia levels in patients who underwent colonoscopy using sedo-analgesia. Methods: Adult patients (n=102), scheduled for procedural sedation, were prospectively analysed. After the induction with propofol and ketamine, infusions of propofol (2 mg kg(-1) h(-1)) and remifentanil (0.05 mcg kg(-1) min(-1)) were started. In Group A, remifentanil infusions were titrated to maintain the ANI value between 50 and 70, whereas in Group C, analgesic requirements were met according to the attending anaesthetist's intention. The heart rate, blood pressure, respiratory rate, SpO(2), BIS, Numeric Rating Scale (NRS) and Ramsay Sedation Scale were monitored. Complications, analgesics consumption, duration of the procedure, demographic information, NRS and the Modified Aldrete Score were evaluated. Results: A total remifentanil amount used in Group A was 66.51 +/- 47.87 mcg and 90.15 +/- 58.17 mcg in Group C (p=0.011); there was no difference in total amounts of ketamine and propofol given. There was a negative correlation between ANI and NRS scores of Group A patients at Minute 0 at the level of 0.402, which was significant statistically (p=0.003). Conclusion: Opioid consumption was diminished when ANI monitoring was used, and thus the patient safety was improved. Further studies with longer procedure times and with a greater number of patients are required to demonstrate whether there is a difference in side effects and recovery times.
Keywords: Analgesia nociception index; colonoscopy; sedation; sedo-analgesia; TOTAL INTRAVENOUS ANESTHESIA; HEART-RATE-VARIABILITY; ANALGESIA/NOCICEPTION INDEX; POSTOPERATIVE PAIN; REMIFENTANIL; PROPOFOL; PREDICTION; PARAMETER; SEDATION; KETAMINE